The relationship between anthropometry and hand grip strength among older Malaysian people / Nurul Shahida Mohd Shalahim - Nurul Shahida, Mohd Shalahim (2016)

(untitled)
Physiological changes and loss of hand grip strength are natural consequences of the ageing process. Previous studies have shown that physiological changes will affect the hand grip strength of elderly people. However, to date, there are no studies which have developed models that predicts the hand grip strength of elderly Malaysians as a function of anthropometric dimensions. Knowledge on the correlation between these variables is crucial in order to create a suitable living environment as well as designing and developing products that cater specifically to the needs of the elderly. Hence, the main objective of this study is to examine the correlation between anthropometric dimensions and hand grip strength in a representative sample of the elderly population in Malaysia and developing the regression models that predicts the hand grip strength of elderly Malaysian males and females. In order to achieve the objectives, a total of ninety one (91) anthropometric dimensions along with hand grip strength data are collected from a sample of 112 subjects aged 60 years and above. The subjects comprises of 56 males and 56 females, recruited from a densely populated urban area in Selangor, namely, Petaling Jaya. The anthropometric parameters are measured using standard anthropometric set whereas hand grip strength is measured using Jamar hydraulic hand dynamometer. Statistical analysis was then carried out to identify the anthropometric dimensions that significantly influence hand grip strength, and the results indicate that only 37 anthropometric dimensions significantly influence the hand grip strength of elderly Malaysians. In addition, the anthropometric dimensions and hand grip strength data were obtained and compared with the data for two age groups (20-30 years and 50-59 years) in order to determine if there is a significant difference in the measurements between these groups. In general, it can be observed that the ageing adult group exhibits lower values for the iv majority of anthropometric parameters and hand grip strength compared to the young adult group. This finding indicates the importance for product designers to gain an understanding on the differences in the physiological dimensions of elderly people with those of other age groups in order to create ergonomic products that account for their special needs. Two regression models have been developed in this study, which predicts the hand grip strength of elderly Malaysian males and females. In both of these models, the hand grip strength is predicted by a regression equation as a function of anthropometric dimensions. A case study has been carried out to validate the prediction models, in which the subjects are required to open bottles of different sizes. Five bottles are chosen for this purpose; the first one, a perfume vial, second, a vitamin supplement bottle, the third, a tall, narrow-mouthed jar of blueberry jam, the fourth, a short, wide-mouthed jar of orange marmalade and the fifth, a mini shower cream bottle. These bottles are typical objects which are available at home and are therefore representative of the actual scenario faced by the elderly. The results indicate that there is a relationship between hand anthropometric dimensions and hand grip strength for elderly Malaysians, whereby the size and surface texture of the lid affects their ability to open the bottles. The significant contributions of this study are as follows. First, the findings of this study can be used to build a database of anthropometric and hand grip strength measurements for the elderly population in Malaysia. Second, the regression models developed in this study can be used as a means to predict the hand grip strength of the elderly populations in Malaysia, which will assist product designers in creating ergonomically designed products. Third, an improved methodology was being proposed in this study which will be useful for researchers who intend to deepen their understanding v on the relationship between anthropometric parameters and hand grip strength of elderly Malaysians.